CT imaging of blunt splenic injury: a pictorial essay - Hassan, Radhiana; Abd. Aziz, Azian; Mohd Ralib, Ahmad Rashid; Abdul Rashid, Mohd Amran; Sa'at@yusof, Azlin; Che Mohamed, Siti Kamariah (2010)
Nonsurgical management has become the standard care for hemodynamically stable patients with splenic injury from blunt abdominal trauma. To attempt nonsurgical management, it is important to identify and characterize not only the splenic injury but also the concurrent injury to solid viscera, bowel and mesentry, or retroperitoneum that may require surgery. The ability of multi-detector row computed tomography (MDCT) to obtain high resolution images has made MDCT the primary imaging modality for the evaluation of these patients. The CT features of splenic injury include lacerations, subcapsular or parenchymal hematomas, active hemorrhage and vascular injuries. A variety of CT grading systems have been proposed to grade splenic injury following trauma. Radiologists should be familiar with the splenic injury grading system to facilitate communication with the managing surgical team and for research purposes. In Hospital Tengku Ampuan Afzan (HTAA), Kuantan, Pahang, from January 2008 to December 2009 there were 42 cases of splenic injuries out of 154 cases of blunt abdominal trauma, which underwent CT assessment. We reviewed all 42 cases of splenic injury and illustrated the spectrum of CT findings based on American Association for the Surgery of Trauma (AAST) classification.